Power output and muscle metabolism during and following recovery from 10 and 20 s of maximal sprint exercise in humans - Bogdanis, G.C.; Nevill, M.E.; Lakomy, H.K.A.; Boobis, L.H. (Acta Physiologica Scandinavica, 1998)
On two separate days eight male subjects performed a 10- or 20-s cycle ergometer sprint (randomized order) followed, after 2 min of recovery, by a 30-s sprint. Muscle biopsies were obtained from the vastus lateralis at rest, immediately after the first sprint and after the 2 min of recovery on both occasions. The anaerobic ATP turnover during the initial 10 s of sprint 1 was 129 ± 12 mmol kg dry weight-1 and decreased to 63 ± 10 mmol kg dry weight-1 between the 10th and 20th s of sprint 1. This was a result of a 300% decrease in the rate of phosphocreatine breakdown and a 35% decrease in the glycolytic rate. Despite this 51% reduction in anaerobic ATP turnover, the mean power between 10 and 20 s of sprint 1 was reduced by only 28%. During the same period, oxygen uptake increased from 1.30 ± 0.15 to 2.40 ± 0.23 L min-1, which partially compensated for the decreased anaerobic metabolism. Muscle pH decreased from 7.06 ± 0.02 at rest to 6.94 ± 0.02 after 10 s and 6.82 ± 0.03 after 20 s of sprinting (for all changes P < 0.01). Muscle pH did not change following a 2-min recovery period after both the 10- and 20-s sprints, but phosphocreatine was resynthesized to 86 ± 3 and 76 ± 3% of the resting value, respectively (n.s. 10- vs. 20-s sprint). Following 2 min of recovery after the 10-s sprint subjects were able to reproduce peak but not mean power. Restoration of both mean and peak power following the 20-s sprint was 88% of sprint 1, and was lower compared with that after the 10-s sprint (P < 0.01). Total work during the second 30-s sprint after the 10- and the 20-s sprint was 19.3 ± 0.6 and 17.8 ± 0.5 kJ, respectively (P < 0.01). As oxygen uptake was the same during the 30-s sprints (2.95 ± 0.15 and 3.02 ± 0.16 L min-1), and [Phosphocreatine] before the sprint was similar, the lower work may be related to a reduced glycolytic ATP regeneration as a result of the higher muscle acidosis.
Keywords: Aerobic metabolism; Anaerobic; Fatigue; Glycolysis; pH; Phosphocreatine; Recovery; Sprinting